The Influence of Celebrity Endorse, Brand Image and Brand Trust on Interest to Buy Make Over Cosmetics - Assyifa, Nadia; Nofirda, Ayu Nofirda Ayu; Akhmad, Ikhbal (Inovbiz: Jurnal Inovasi Bisnis, 2024)
This study aims to determine as well as identify impact of celebrity endorse, brand image and brand trust on intention in purchasing Make Over brands in Pekanbaru. Research uses quantitative method by utilizing the research sampling model, namely non-probability sampling model, a method which does not give every component or fellow of population equal opportunities or chances to choosen as a sample. Research used purposive sampling technique, videlicet sampling according to specific trait and considerations with overall sample are 105 Make Over cosmetic users. Data analysis method utilized in this research is multiple linear regress Â analysis utilizing SPSS 26. Results of the study are celebrity endorsement variable owns a positive and significant influence on variable of purchasing Make Over brands attraction in Pekanbaru, the brand image variable has a good and huge effect on the variable of interest in buying Make Over brands in Pekanbaru city, and brand trust variable has a favorable and significant effect on the interest variable in purchasing Make Over cosmetics in Pekanbaru.